Pengaruh Implementasi Revit-BIM terhadap Akurasi Quantity Take-Off Struktur Pada Proyek Bangunan Komersial - Ganjar Jojon Johari; Lutfi Lukmanul Hakim (Institut Teknologi Garut, 2026)
This study aims to analyze the effect of implementing Building Information Modeling (BIM) using Autodesk Revit on the accuracy of structural Quantity Take-Off (QTO) in the Abelia Resto & Gallery project. Detail Engineering Design (DED) data and the Cost Budget Plan (RAB) were modeled in Revit 2024 to generate volume and cost estimates for concrete and reinforcement, which were then compared with manual calculation results. The results show that the average volume deviation is below 5%, except for the gallery foundation (-15.32%) and the restaurant floor slab (-9.60%). Concrete cost estimates generated using Revit are lower than those obtained through manual methods, with deviations of -4.65% for the restaurant and -1.57% for the gallery, while reinforcement costs decreased for the restaurant (-9.68%) and increased for the gallery (3.82%). These differences are caused by the quality of input data, the level of modeling detail, and differences in assumptions used in manual methods. The study concludes that Revit-BIM is capable of improving the accuracy and efficiency of the QTO process for structural works, although field verification is still required to ensure conformity with actual site conditions. This research recommends the use of Revit-BIM as the primary supporting tool for project cost estimation, particularly at the early planning stage, to improve quantity accuracy and calculation time efficiency.